2010
DOI: 10.1590/s0004-282x2010000200025
|View full text |Cite
|
Sign up to set email alerts
|

Reaction time assessment in children with ADHD

Abstract: Attention deficit, impulsivity and hyperactivity are the cardinal features of attention deficit hyperactivity disorder (ADHD) but executive function (EF) disorders, as problems with inhibitory control, working memory and reaction time, besides others EFs, may underlie many of the disturbs associated with the disorder. Objective: To examine the reaction time in a computerized test in children with ADHD and normal controls. Method: Twenty-three boys (aged 9 to 12) with ADHD diagnosis according to Diagnostic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 21 publications
0
15
0
12
Order By: Relevance
“…The control group followed the same criteria for gender, age and IQ. The results showed that the ADHD group indicated reaction time higher than normal controls and a graduated loss of sustained attention [52].…”
Section: Paper Special Education and Ictsmentioning
confidence: 89%
“…The control group followed the same criteria for gender, age and IQ. The results showed that the ADHD group indicated reaction time higher than normal controls and a graduated loss of sustained attention [52].…”
Section: Paper Special Education and Ictsmentioning
confidence: 89%
“…As the EFs are a group of cognitive functions that include inhibition, response selection and alteration, behavioural monitoring and WM, it is considered that children with ADHD exhibit a range of difficulties, which results in a worse performance compared to individuals without ADHD 6,7,10,25,26,27,28,29,30 . Our results are consistent with many studies on neuropsychological evaluation and ADHD, showing an improvement in WM, IC, and MF, as well as a relevant medication effect on EF performance at various levels 11,13,15,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…O sistema atencional anterior desenvolvido pelo córtex frontal exerce atividade regulatória ao estabelecer conectividade global inibitória do CPF com outras regiões e participa conjuntamente do núcleo estriado do planejamento das respostas motoras (Bolfer et al, 2010;Farrant & Uddin, 2015). O CPF possibilita o planejamento, a verificação, a seleção e a concentração ao estabelecer o direcionamento da consciência, a seleção e o foco da atenção (Luria, 1981).…”
Section: Anatomia E Neurofisiologia Da Atençãounclassified
“…O sistema atencional posterior formado pelo córtex parietal, núcleos talâmicos e estruturas mesencefálicas associa-se com o controle do processamento perceptual automático e a atenção explícita ou voluntária, isto é, com mecanismos atencionais bottom-up (Bolfer et al, 2010;Farrant & Uddin, 2015). O tálamo interliga o mesencéfalo ao córtex, recebe e seleciona inputs sensoriais, direciona o processamento da atenção para áreas que devem detectar o alvo (córtex occipto-parietal) e gerar respostas (Portas et al, 1998).…”
Section: Anatomia E Neurofisiologia Da Atençãounclassified
See 1 more Smart Citation